Approaching the Optimal Performance of Nonlinear OFDM With FWA Techniques - Basílio, Diogo Francisco Frederique (2019)
Telecommunications are part of people’s daily lives. Also, nowadays, a complete "technological illiteracy" is hard to be found in the so-called developed countries. To the point of being almost a necessity in everyday life, telecommunications must evolve to meet this need. One of the most widely used transmission techniques in mobile communications today is Orthogonal Frequency-Division Multiplexing (OFDM). Adopted in the fourth generation of mobile communications (4G), much for its ability to deal with frequency-selective channels and good spectral efficiency, it is one of the candidate schemes to be in the fifth generation of mobile communications (5G). Despite the advantages, OFDM signals have high envelope fluctuations, making them sensitive to nonlinear effects. Several techniques were proposed to reduce these fluctuations, however they required nonlinear operations that worsened the performance of receivers. Nevertheless, it has recently been shown that the distortion effects caused by nonlinearity is no longer seen as a problem, but as information. In fact, with this discovery, it becomes possible to employ optimal receivers in order to improve the performance. Despite that, these receivers have a very high complexity and, to try to solve this problem, sub-optimal receivers have been proposed. The sub-optimal receiver presented in this thesis is based on an optimization algorithm called Fireworks Algorithm (FWA). The thesis includes: a study of the parameters of the algorithm in order to understand its true impact on Bit Error Rate (BER) performance; a comparison of the BER for different channels: Additive White Gaussian Noise (AWGN) and Frequency-Selective; and a proposal for an FWA variant that tries to reduce the receiver’s complexity even more.